2014
DOI: 10.1007/s13365-014-0295-x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive disorders in HIV-infected and AIDS patients in Guangxi, China

Abstract: The purposes of this study were to assess cognitive disorders in HIV/AIDS patients, identify the prevalence of HIV-associated neurocognitive disorders (HAND), provide evidence that may be used for early diagnosis and treatment, and establish a baseline for follow-up studies. The setting for this study was Guangxi, a culturally and economically underdeveloped province located in southwestern China with a large minority community. Due to the specific geographic and cultural environment, Guangxi has the second hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
1
12
0
1
Order By: Relevance
“…La prevalencia de demencia asociada a VIH es del 5 % y está aumentando a nivel mundial [24]. El cuadro se caracteriza por ser crónico, progresivo, con deterioro cognitivo que debe afectar significativamente a las actividades de la vida diaria y la conducta [17].…”
Section: Discussionunclassified
“…La prevalencia de demencia asociada a VIH es del 5 % y está aumentando a nivel mundial [24]. El cuadro se caracteriza por ser crónico, progresivo, con deterioro cognitivo que debe afectar significativamente a las actividades de la vida diaria y la conducta [17].…”
Section: Discussionunclassified
“…The incidence of human immunodeficiency virus (HIV) infection shows regional variations (1). Guangxi has the second-highest prevalence of patients with HIV and mortality because of HIV infection in China (2). The data from the China Centers for Disease Control Epidemic Information System reported that Guangxi had 85,576 cases of HIV infection and AIDS and 49,109 cases of death following HIV infection in December 2018.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the regions with the fastest growing HIV epidemic in China, Guangxi has reported a total of 124,282 HIV/AIDS cases by the end of 2017, indicating a 78.7% increase since June 2011 (69,548 HIV/AIDS cases) and placing Guangxi second among 31 Chinese provinces in terms of HIV seropositive cases [22, 23]. The HIV epidemic in Guangxi is largely characterized as a rural phenomenon with many PLWH being rural residents, having low socio-economic status, and being infected mainly through sexual contacts [24].…”
Section: Introductionmentioning
confidence: 99%